A Model Driven Application Framework for Managed Processes - Tegegne, Abel A (University of Ottawa (Canada), 2010)
Organizations are frequently expected to improve operational efficiency through effective decision making. Effective decision making, among other things, requires a configurable business process application platform that can be used to execute, monitor and manage processes involving people, teams, departments, organizational units and their multiple applications. This kind of platform facilitates data collection for performance management and analysis for measuring quality of service delivery and business process optimization. It also facilitates collaboration between process participants, regulatory compliance, configurability to fit to changing requirements and accelerates decision making by sensing actionable events. Healthcare is a significant area where such a platform can be of great use for monitoring patient care. Patient care monitoring applications are data intensive and require medical guidelines based collaboration between patients, individuals, care providers and organizational units. These applications should provide performance management information to measure the quality of healthcare service delivery processes. These types of applications must also be configurable to adapt to frequently changing types of business events and the process of collect event data. This thesis proposes a model driven application framework that can be used to create configurable process oriented applications that can be customized to the current needs of an organization. The proposed framework also provides the ability to monitor, manage and report on processes and collected event data. A healthcare scenario is used to illustrate and validate our approach by building a patient monitoring application.
Keywords: Economics, Commerce-Business.; Engineering, System Science.